Audit Awal Energi Listrik RS Kartika Husada Tambun - Saingin, Bungaran; Krismahariyanto, Mei; Fahdillah, Narulita (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2019)
Energy evaluation is an important means for an organization to be more competitive in the global era. IKE or the intensity of electricity consumption is a term used to evaluate energy consumption in a system (building). IKE value is obtained by comparing the total use of electrical energy in building area. The evaluation process is done by collecting historical data from Kartika Husada Tambun hospital building., such as data of building area, data of the use of electricity, and the budget spent of electricity needs. From the calculation results, IKE value of the Kartika Husada Tambun Hospital in 2016 was 160,73 kWh / m2/ year, the IKE value in 2017 was 166,04 kWh / m2/ year, and 2018 was 142,79 kWh / m2/ year. This result is in the efficient category because it does not pass the IKE standard for electricity for a hospital building of 380 kWh / m2 per year. For cost savings the author recommends the application of energy-saving technology